How live streamers can motivate consumers' purchase intention: an empirical study based on social presence, trust, and innovation acceptance - Xie, Qing; Mahomed, Anuar Shah Bali; Mohamed, Rosmah; Subramaniam, Anusuiya (Human Resources Management Academic Research Society (HRMARS), 2024)
Consumer purchase intention is the necessary element for organizational success and needs experience researchers’ emphasis. Hence, the current article examines the role of live streamers’ social presence, trust and innovation acceptance on the consumer purchase intention in retail businesses in China. The article also investigates the mediating role of consumer trust among live streamers’ social presence, trust, and consumer purchase intention in retail businesses in China. The researchers have followed the primary data collection methods and extracted the questionnaires for data collection. The researchers also applied the smart-PLS to examine the relationships among variables. The results indicated that the live streamers’ social presence, trust, and innovation acceptance have a positive nexus with consumer purchase intention. The findings also indicated that consumer trust significantly mediates among live streamers’ social presence, trust, and consumer purchase intention in retail businesses in China. This article guides the policymakers in establishing policies related to improving the consumer purchase intention that enhances the organizational presence.